DEVELOPMENT OF LEARNING DEVICES ON CIRCLE MATERIALS IN SMP/MTs BASED ON ART/WOVEN AS A SOUTHWEST ACEH COMMUNITY CULTURE - Cut Maulidian; Lukman Ibrahim; Zainal Abidin; Novi Trina Sari (Jurnal Ilmiah Pendidikan dan Pembelajaran Matematika, 2022)
Purpose The use of media that is around students is believed to be very effective in maximizing the learning process. Every day students carry out activities both at home and outside the home, when they are active they are often faced with something that can be related to mathematical material. Such media can be applied to learning tools and developed properly through or by using the local wisdom culture of an area that is focused on cultural experiences contained in the local community environment. Mathematics learning must undergo changes in the context of improving the quality of education so that it can improve learning outcomes. optimal. So that efforts continue to be made to realize an innovative learning in accordance with the times and technology. This type of research is development research using a 4D model consisting of four stages. The second stage, the design includes the design of the RPP, LKPD, Teaching Materials, and Evaluation Sheets. The third stage of development includes product creation and validation carried out by mathematicians. The research instrument used a validation sheet and a teacher response questionnaire. The validity of the tools obtained by the RPP is 84.37%, LKPD 88.11%, teaching materials 85.07% and evaluation sheets 85.77%. The practicality of the equipment is in the very good category with an average gain of 4.26. It can be concluded that learning tools are considered valid and practical.Keyword : Development, Learning tools,Based on, Art of weaving, 4-D